Navigated renal access using electromagnetic tracking: an initial experience - Huber, Johannes; Wegner, Ingmar; Meinzer, Hans-Peter; Hallscheidt, Peter; Hadaschik, Boris; Pahernik, Sascha; Hohenfellner, Markus (Surgical endoscopy and other interventional techniques, 2011)
Background and aim: Navigation systems are promising tools for improving efficacy and safety in surgical endoscopy and other minimally invasive techniques. The aim of the current study is to investigate electromagnetic tracking (EMT) for navigated renal access in a porcine model. Methods: For our proof-of-principle study we modified a recently established porcine ex vivo model. Via a ureteral catheter which was placed into the desired puncture site, a small sensor was introduced and located by EMT. Then, a tracked needle was navigated into the collecting system in a “rendezvous” approach. A total of 90 renal tracts were obtained in six kidneys using EMT, with a maximum of three punctures allowed per intervention. For each puncture, number of attempts to success, final distance to probe, puncture time, and localization were assessed. We compared absolute and relative frequencies using the chi-square test and applied the Mann–Whitney U-test for continuous variables. Results: No major problems were encountered performing the experiment. Access to the collecting system was successfully obtained after a single puncture in 91% (82/90) and within a second attempt in the remaining 9% (8/90). Thus, a 100% success rate was reached after a maximum of two punctures. Location of the calyx did not have a significant effect on success rate (p = 0.637). After a learning phase of 30 punctures, higher success rate (96% versus 83%; p = 0.041) was accomplished within shorter puncture time (14 versus 17 s; p = 0.049) and with higher precision (1.7 versus 2.8 mm; p < 0.001). Conclusions: With respect to other established techniques, use of EMT seems to decrease the number of attempts and procedural time remarkably. This might contribute to greater safety and efficacy when applied clinically. The presented approach appears to be promising, especially in difficult settings, provided that in vivo data support these initial results.